Proposal framework to activate the international accounting procedures for disasters and wars effects in the local environment - عبدالحليم, صفوان قصي; جاسم, جعفر جواد (Journal of Economics and Administrative Sciences, 2017)
natural and non-natural disasters, is an environmental challenges the society and the economy as well as a direct and indirect economic affect, and the units are part of the system overlapping among themselves and thus affected by external indicators, directly or indirectly, these direct effects appear in the destruction or damage inflicted by disasters in property , infrastructure , superstructure , accounting information systems and indirectly in the outcome of future business, comes research problem through access to accounting treatments issued by the Federal Office of financial supervision to address the damage caused by the disasters and prepare the missing financial accounts it turns out us that there is negligence of a number of issues that we believe need to be discussed and to propose appropriate mechanisms to address them. The importance of research is needed for decision-makers at all levels to a high-quality accounting information about the value of the damage caused as a result of disasters suffered by Iraq for more than once in recent decades, and the presence of a number of accounting topics actors and absent from the local accounting procedures and requires the review and update accounting treatments approved by the Board of Supreme Audit to respond to the needs of decision makers first and to blend in with a private international requirements. This research depended on main hypothesis which refers to:(that building a system of accounting information in light of disasters responds to the need of the decision-maker requires renovation local accounting procedures in order to be more effective in the light of international applications .The research has reached a number of conclusions including integrated accounting system is short of meeting the international financial reporting requirements as a result of not admitting much of the accounting procedures when disasters occur distorts the financial statements as they relate to the value of the losses incurred from the impact of disasters.                                               The researcher found a set of recommendations including , The need to adapt international accounting procedures in light of disasters and wars in the local environment through the introduction of new items in the consolidated accounting manual, which applies in the Iraqi companies with customizable directory number and restrictions and to explain the item and the international standard which is based on the newly created item.